Bibliometric analysis of postgraduate dissertations on Qur’an and Sunnah studies: a review towards new prospects in integration of knowledge - Mohd Marzuki, Zunaidah (2018)
Bibliometric analysis which is based on content or citation analysis is often used in the field of Library and Information Sciences (LIS) and other sciences. Occasionally, it has also been used to analyze several patterns of publication in Islamic studies. There are many articles on bibliometric analysis of dissertations and theses in various fields too. However, in integration of knowledge (IOK), there is no research being done on postgraduate dissertations on Qur’an and Sunnah studies from different programs in International Islamic University Malaysia. This study will use bibliometric analysis to review various patterns of completed and ongoing dissertations, hence giving suggestion towards new prospects in integration of knowledge for research in Qur’an and Sunnah studies. The study will explore patterns according to department/kulliyyah and type of dissertation. This study will recognize which subject areas are successfully achieved by IOK and which areas needed to fill the gap. Perhaps through the result of this study, it will help researchers particularly postgraduate students from different backgrounds to incorporate knowledge from Qur’an and Sunnah in their study and researchers from Qur’an and Sunnah studies to integrate different subject areas in their research.